Political Philosophy of Eurasianism: Paradigmatic Foundations and Their Limitations - Plebanek, Olga; Pyzh, Vladimir; Rosenko, Svetlana; Ретrov, Sergеу (Տիգրան Մեծ)
The article examines, in relation to the data of mod-ern science and current geopolitical trends, the key ideas of the founders of Eurasianism, analyzes the transformation of the ideology of Eurasianism in the modern ideological and political space of Russia. The authors pay attention to the concepts of “neo-Eurasianism” and attempts to revive Eura-sian ideas and supplement them with new original views. Eurasianism, being one of the largest and most significant philosophical, political and ideological projects of the XX century, as well as neo-Judaism, which became its logical continuation, attracted the attention of a large number of both supporters and opponents
Keywords: Political Philosophy